2016
DOI: 10.1007/978-3-319-27069-2_5
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Post-transcriptional Control of Metabolism

Abstract: Circadian clocks control thousands of genes, which ultimately generate rhythms in signaling pathways, metabolism, tissue physiology and behavior. Although rhythmic transcription plays a critical role in generating these rhythmic gene expression patterns, recent evidence has shown that post-transcriptional mechanisms are also important. Here we describe studies showing that regulation of mRNA poly(A) tail length is under circadian control and that these changes contribute to rhythmic protein expression independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
2
0
1
Order By: Relevance
“…1We note several excellent studies revealing that post-transcriptional regulation of RNA processing and small interfering RNA-mediated RNA silencing have also been strongly implicated in circadian control, as well as both global and specific regulation of protein synthesis rates [38,98,229, 230, 231, 232, 233, 234, 235, 236]. Whilst perturbation of these essential cellular processes clearly affects circadian gene expression rhythms, to our knowledge it has not been demonstrated that their rhythmic regulation is essential for timekeeping competence and we thus direct the interested reader to these excellent reviews [237, 238, 239]. …”
mentioning
confidence: 99%
“…1We note several excellent studies revealing that post-transcriptional regulation of RNA processing and small interfering RNA-mediated RNA silencing have also been strongly implicated in circadian control, as well as both global and specific regulation of protein synthesis rates [38,98,229, 230, 231, 232, 233, 234, 235, 236]. Whilst perturbation of these essential cellular processes clearly affects circadian gene expression rhythms, to our knowledge it has not been demonstrated that their rhythmic regulation is essential for timekeeping competence and we thus direct the interested reader to these excellent reviews [237, 238, 239]. …”
mentioning
confidence: 99%
“…The PAR family proteins form homodimers or hetero-dimerize within other family proteins and function as either transcription activators or repressors (Hai & Hartman 2001). The PAR family proteins have been found to have diverse physiological functions in mammals, including circadian rhythms, immunoregulation, and cancer development (Green 2016). This review will focus on the role of E4 promoter-binding protein 4 (E4BP4), also named as nuclear factor, interleukin 3 regulated (NFIL3), the least known PAR transcription factor, in liver metabolic regulation.…”
Section: Introductionmentioning
confidence: 99%
“…A dinâmica e modulação dessas alças interligadas ocorrem em um período de 24 horas (Bass & Takahashi, 2010). Foi visto também que a acetilação e modificação de histonas possuem relação com a transcrição circadiana dos genes do relógio, como por exemplo a nocturnina, expressa de forma rítmica e com pico durante a noite, que atua também como estabilizador de RNAm (Green, 2016). É sabido que vários componentes que regulam o metabolismo estão sob um rigoroso controle temporal, demonstrando máximos e mínimos de atividade ao longo do dia, permitindo assim uma separação temporal de processos bioquímicos e fisiológicos (Asher & Schibler, 2011;Asher & Sassone-Corsi, 2015).…”
Section: Relógio Biológicounclassified